Applied Regression Modelling to Recommend Sustainable Tourism Development Policies: A Case Study of Danang City in Vietnam - Tien, Nguyen Duc (Bright Publisher, 2024)
Sustainable tourism development is one of the top focuses not only in Vietnam but also around the world. Especially when Covid-19 began to break out in early 2020, causing most tourism activities to stop and causing many communities that considered tourism to be completely independent from other industries to have time to look back. Thus, the article aims to identify the main factors contributing to sustainable tourism development in Danang City, Vietnam. Accordingly, some contents need to clarify factors affecting sustainable tourism development, measuring the characteristics and the role of each factor impacting sustainable tourism development. Finally, policy implications for sustainable tourism development in the future are proposed. Based on the goal, the author surveyed 600 tourists and used the regression modeling method from data processed using SPSS 20.0. In addition, the results showed six factors affecting sustainable tourism development with a significance of 0.01. This situation requires more practical recommendations from state management agencies and tourism enterprises. The contributions of this study suggest sustainable tourism development policies to balance economic development, social stability, and environmental protection. The article evaluates sustainability, considering the cohesion and balance of sustainable development aspects, such as economic, social, and environmental, thereby going deeper and identifying groups of activities. The main drivers to achieve sustainable tourism development include economics, society, environment, tourism resources, tourism products and services, and infrastructure. The research novelty discusses proposed six recommendations, which include (1) infrastructure development, (2) developing technical facilities for the tourism industry, (3) developing human resource training, (4) level of organization and management of the tourism industry, (5) quality of tourism services, and (6) community participation for sustainable tourism development in Danang City, Vietnam.